Salt Industry and the Economy of Ebonyi State, Nigeria, in the PreColonial Era - Ongele, Festus Nwankwo; Anyigor, Judemary Ikechukwu; Ellah, Timothy Ogbang; Effiong, Eke Nta (Pinisi Journal of Social Science, 2025)
Salt deposit is one of the mineral deposits that are found in different parts of Igboland before the colonial administration. Its contributions to the economic development of the people are drawn from its extraction, processing and distribution. The study was anchored on Linkage Theory developed by Albert Hirschman. This theory suggests that a leading sector, such as the salt industry can drive economic growth and development through its linkage with other sectors. Data were generated from primary and secondary sources. They were analysed qualitatively, using content analysis to identify that the industry was an important source of revenue and employment to numerous residents of the communities that are presently captured as Ebonyi State, including areas that are not limited to communities of Afikpo, Edda, Ezza, Okposi, and Uburu. Acknowledging its impact on the economy of the state, its negative effects, such as environmental and health risks, and challenges were investigated. It is discovered that the management practices, involving use of local skills, manual mining approach, and active involvement of aged women are inadequate and could not sustain a long-term extraction, processing, and distribution of the wealth for sustainable profit maximization. So, the enterprise requires a thoughtful and problem-solving policy that could create a conducive environment for achieving profit-oriented salt mining. Implementation of such a scheme would involve active participation of entrepreneurs (vibrant males and females) with decisive support from the government in areas of policy-making and subsidizing the cost of mechanising the industry.